Regional versus individual aspects of the digital divide in Germany - Katrin Schleife (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper analyzes the regional dimension of the German digital divide. It considers the impact of regional characteristics on differences in the share of Internet use between German counties. In addition, it studies the influence of regional factors as well as individual characteristics on the individual probability of becoming a new Internet user. Based on two large data sets, SOEP and INKAR, the analyses show that it is not the rusticity of a region itself that explains regional differences in Internet use. The results rather indicate that it is the different composition of the population between rural and urban areas that accounts for the regional digital divide.
More recent version: http://hdl.handle.net/10419/27573
Keywords: O33; R20; O18; 330; digital divide; Internet use; regional differences